The Effect of Guided Discovery Learning Model on the Science Process Skills of Students in State VII Bangil Middle School Class VII on Environmental Pollution Materials - Sabila Nurul Adilah; Nur Efendi (International Consortium of Education and Culture Research Studies, 2020)
This study aims to determine the effect of Guided discovery learning models on the science process skills of students in SMP Negeri 3 Bangil class VII on the material of environmental pollution. This type of research is quasi experimental, with non equivalent design pre-test and post-test control group. The sampling technique used purposive sampling obtained 2 classes, namely class VII G as a control class and class VII H as an experimental class. The instrument of this research is a test of science process skills in environmental pollutants with data collection techniques using the test method, namely pre-test and post-test. Data analysis techniques were carried out using the t-test. The results showed that the Guided discovery learning model had a significant effect on the science process skills of students in SMP Negeri 3 Bangil class VII on the material of environmental pollution.